2020
DOI: 10.3390/cells9030678
|View full text |Cite
|
Sign up to set email alerts
|

Silibinin Attenuates Silica Dioxide Nanoparticles-Induced Inflammation by Suppressing TXNIP/MAPKs/AP-1 Signaling

Abstract: Silica dioxide nanoparticles (SiONPs) have been applied to several fields, such as drug delivery and gene therapy. However, SiONPs are a constituent of fine dust and can induce excessive inflammatory responses in the lungs via the airways. Silibinin, a major component of silymarin, has been known for its anti-oxidant and anti-inflammatory effects. In the present study, we explored the protective effects of silibinin against SiONPs-induced airway inflammation and explored its underlying mechanism of action, foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 39 publications
3
15
0
Order By: Relevance
“…Moreover, melatonin treatment alleviates the pulmonary inflammation associated with cigarette smoke-induced COPD by suppressing MAPK phosphorylation [21]. In this study, SiONPs induced the inhibition of several inflammatory mediators as previously reported [15,16]. However, treatment with melatonin reduced the inflammatory index, including those of inflammatory cells and cytokines, in both the SiONPs-exposed mice and SiONPs-stimulated cells.…”
Section: Discussionsupporting
confidence: 80%
“…Moreover, melatonin treatment alleviates the pulmonary inflammation associated with cigarette smoke-induced COPD by suppressing MAPK phosphorylation [21]. In this study, SiONPs induced the inhibition of several inflammatory mediators as previously reported [15,16]. However, treatment with melatonin reduced the inflammatory index, including those of inflammatory cells and cytokines, in both the SiONPs-exposed mice and SiONPs-stimulated cells.…”
Section: Discussionsupporting
confidence: 80%
“…S4F). Importantly, some of these genes (THBS1, MAPKAPK2, CD9, TXNIP) were strongly associated with IL-6 signaling (Lim et al, 2020;Lopez-Dee et al, 2011;Shi et al, 2017), indicating that IL-6 or its associated genes are associated with metastatic tumors, in alignment with our previous findings. Overall, these findings may explain the increased myeloid bias in met-high compared to met-low tumors.…”
Section: Il-6 Is a Key Player In The Crosstalk Between Hscs And Tumorsupporting
confidence: 90%
“…Furthermore, to strengthen the involvement of IL-6 in met-high tumors, transcription signatures of CD45+ stroma cells obtained from the tumor microenvironment of B16 melanoma, assessed by NanoString approach, revealed seven upregulated genes, including THBS1, MAPKAPK2, CD9, TXNIP, CD24, ITGA5, and SYK (online supplemental figure S5D). Importantly, some of these genes (THBS1, MAPKAPK2, CD9, TXNIP) were strongly associated with IL-6 signaling, [29][30][31] indicating that IL-6 or its associated genes are coupled with metastatic tumors, in alignment with our previous findings. Overall, these findings may explain the increased myeloid bias in met-high compared with met-low tumors.…”
Section: Il-6 Promotes Mdp Proliferation and Differentiationsupporting
confidence: 89%